Annual Report, 1998 - World Trade Organization; Centre for Curriculum, Transfer and Technology, Victoria (British Columbia). (Washington, D.C. : World Trade Organization, 1998)
The annual report of the Centre for Curriculum, Transfer and Technology (British Columbia) summarizes the educational and operational activities of the year and signals important shifts in direction. Working with partners in the college, university college, institute and agency system, and with associates in universities and secondary schools, the Centre manages more than 300 separate projects and initiatives for the Ministry of Advanced Education, Training and Technology. An extensive consultation with administrators, faculty, and students has led to the creation of a document entitled Strategic Directions: A New Emphasis for the Centre for Curriculum, Transfer and Technology. In Prior Learning Assessment (PLA), the Centre is shifting from supporting the expansion of PLA to assisting institutions to improve the ways in which all assessment is conducted. Over the past year, the Centre has undergone significant organizational restructuring in order to become more service-oriented, integrated, flexible and cost efficient. Last year, the Centre provided consulting services in the area of Learning Outcomes by delivering presentations and workshops about curriculum and program development at 15 institutions in order to build on the outcomes and assessment expertise that exists in BC. Appendix shows a list of documents that have been submitted to the Ministry of Advanced Education, Training and Technology. (JA)
Microfiche.
Keywords: College Outcomes Assessment; Foreign Countries; Government Role; Higher Education; Institutional Evaluation; Organizational Effectiveness; Partnerships in Education; Program Evaluation; Public Education; Schools; British Columbia; Reports, Descriptive